2020
DOI: 10.1152/ajprenal.00079.2020
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy and safety of a system for sorbent-assisted peritoneal dialysis

Abstract: A system for sorbent-assisted peritoneal dialysis (SAPD) was designed to continuously recirculate dialysate via a tidal mode using a single lumen peritoneal catheter with regeneration of spent dialysate by means of sorbent technology. We hypothesize that SAPD treatment will maintain a high plasma-to-dialysate concentration gradient and increase the mass transfer area coefficient of solutes. Thereby, the SAPD system may enhance clearance while reducing the number of exchanges. Application is envisaged at night … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…In addition, slow equilibration between plasma and intraperitoneal compartment in the pig limited lactate release. In vitro, we have demonstrated that cumulative base release by the nighttime system is sufficient (≥70 mmol) in case of metabolic acidosis (van Gelder, Ligabue, et al, 2020). Importantly, the capacity of the sorbents to release bicarbonate is highly concentration-dependent, an important safety characteristic of the device.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, slow equilibration between plasma and intraperitoneal compartment in the pig limited lactate release. In vitro, we have demonstrated that cumulative base release by the nighttime system is sufficient (≥70 mmol) in case of metabolic acidosis (van Gelder, Ligabue, et al, 2020). Importantly, the capacity of the sorbents to release bicarbonate is highly concentration-dependent, an important safety characteristic of the device.…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, solute concentrations in peritoneal effluent entering the SAPD system were low, accounting for the low absolute removal by the system. Of note, in vitro studies showed that in case of higher toxin delivery to the system the capacity of the system was sufficient to remove the daily toxin production (van Gelder, Ligabue, et al, 2020). The increase of the MTAC during SAPD treatment (1.1-to 1.3-fold for urea and 1.2-to 2.3-fold for creatinine vs. a static dwell) was lower than previously reported in patients treated with CFPD (1.5-to 2.5-fold for urea and 1.4-to 2.5-fold for creatinine) (Amerling et al, 2001;Cruz et al, 2001;Freida & Issad, 2003;Raaijmakers et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although peritoneal dialysis is associated with less life-style restriction for patients compared with hemodialysis, storage and transportation of dialysate are still an issue for patients and limit their daily activities. Several peritoneal dialysis-based wearable devices are under development currently including the AWAK project by AWAK Technologies (Singapore) [53], the WEAKID project by Nanodialysis Inc (Oirschot, The Netherlands) [52,99], and CarryLife project by Triomed (Lund, Sweden) [51].…”
Section: Wearable Artificial Kidneysmentioning
confidence: 99%
“…Several human trials for peritoneal dialysis-based wearable devices are still under study. Current published research revealed sufficient dialysis clearance without severe adverse events [53,99]. Abdominal discomfort is the most common side effect [53].…”
Section: Wearable Artificial Kidneysmentioning
confidence: 99%
“…[30]. Andere Verfahren verwenden zusätzlich Austauscherharze oder versuchen, durch Dilution eine Harnstoffelimination zu erreichen [35]. Darüber hinaus werden photo-und elektrooxidative Verfahren für die Lösung des "Harnstoffproblems" getestet [14].…”
Section: » Metaanalysen Konnten Hinsichtlich Mortalität Und Technischem üBerleben Keinen Vorteil Für Low-gdp-lösungen Belegenunclassified